Evaluasi Kebijakan Penyelenggaraan Reklame di Kabupaten Kuantan Singingi - Suheri Rambe; Muhammad Sufiansah; Zulkarnaini Zulkarnaini (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This research aims to evaluate the effectiveness of advertising policy in Kuantan Singingi Regency using qualitative methods and a phenomenological approach. The policy evaluation theory used is William N. Dunn's model, which emphasizes six success criteria, namely effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. Data was collected through interviews, observation and documentation, and analyzed using interactive data analysis. The research results show that advertising policies have not been fully effective in achieving the expected goals, such as increasing regional income and arranging the aesthetics of the city. Findings indicate the existence of illegal advertisements that hinder tax revenues and public dissatisfaction with the government's response to their complaints. Even though the resource structure is in place, implementor skills need to be improved to achieve better efficiency. Licensing and supervision procedures are also considered inadequate, and policies do not provide equal opportunities for all business actors, especially small businesses. This research provides recommendations for improving future policy implementation, with the hope of increasing effectiveness and responsiveness to community needs.